Infliximab in patients with active ankylosing spondylitis: experience at Hospital Nacional Edgardo Rebagliati Martins - Montero, Manuel (2007)
Infliximab is effective in treating patients with ankylosing spondylitis (AS). However, its cost makes its indiscrimate use prohibitive. Objective: To determine whether an induction regimen with infliximab remained effective over time in a group of patients with active AS. Design: Exposed only. Setting: Rheumatology Service, Hospital Nacional Edgardo Rebagliati. Participants: Patients with active and refractory ankylosing spondylitis. Interventions: Infliximab, administered at weeks 0, 2 and 6. One patient received doses of 3 mg/kg and the remaining patients received 5 mg/kg of infliximab. All patients continued their treatment with sulfasalazine. Main outcome measures: We determined the proportion of patients achieving ASAS 20, ASAS 40 and Bath ankylosing spondylitis disease activity index - BASDAI 50 at last assessment (median of 55 weeks). Results: At last observation, five patients (71,4%) had a sustained ASAS 20 response. Four (57%) and three (43%) patients remained responders according to the BASDAI 50 and ASAS 40 respectively.Three patients (43%) relapsed, with mean time of 26,6 weeks. No serious adverse events were observed. Conclusions: The infusion of three doses of infliximab is effective to control disease activity in patients with refractory AS. In some patients, effectiveness remained for a prolonged period of time.